2005
DOI: 10.2320/matertrans.46.2461
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Equations for Bubble Formation Frequency from Downward-Facing Nozzle with and without Rotating Flow Effects

Abstract: Bubble formation from a downward-facing single-hole nozzle immersed in a still circular water bath has been observed with a high-speed video. An empirical equation is derived for the frequency of bubble formation, f B0 , as a function of gas flow rate Q g , the inner and outer diameters of the nozzle, d ni and d no , the acceleration due to gravity, g, and the physical properties of fluids. A cross-flow is imposed on the nozzle by rotating the bath around its vertical axis. The frequency of bubble formation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Then, a kind of transition occurs, where F increases with q, and reaches a local maximum at about 3.5 l/s. The order of magnitude of F is perfectly consistent with data reported in literature (Neven, 2005;Goda et al, 2005). In contrast, the experimentally determined bubble diameters are a new piece of information.…”
Section: Effect Of the Gas Flow Ratesupporting
confidence: 90%
See 2 more Smart Citations
“…Then, a kind of transition occurs, where F increases with q, and reaches a local maximum at about 3.5 l/s. The order of magnitude of F is perfectly consistent with data reported in literature (Neven, 2005;Goda et al, 2005). In contrast, the experimentally determined bubble diameters are a new piece of information.…”
Section: Effect Of the Gas Flow Ratesupporting
confidence: 90%
“…At low submergence depths indeed, it is observed that the bath enters into a swirling motion, which may induce a premature detachment of the bubbles, and thus a higher frequency. Goda et al (2005) claim that the natural bubbling frequency can be multiplied by up to 3 with bath rotational velocities of only 0.2 m/s (for lance exit velocities between 1.5 and 20 m/s). It appears clearly in Fig.…”
Section: Effect Of the Lance Submergence Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the downward bubble formation has received much less attention than the upward injection. More recently this configuration was considered by Tsuge et al, 5 Goda et al 6 and Wollants et al, 7 but always in flow conditions quite different from the ones considered in the present study. Tsuge et al 5 considered downward bubble injection with flow rate lower than that in the current study by 2 orders of magnitude (0.034 m 3 /h) and a ratio between the injection nozzle diameter and height clearance larger than 1, which leads to the absence of formation of air cavity and a flow with much lower inertial effects.…”
Section: Literature Surveymentioning
confidence: 76%
“…Tsuge et al 5 considered downward bubble injection with flow rate lower than that in the current study by 2 orders of magnitude (0.034 m 3 /h) and a ratio between the injection nozzle diameter and height clearance larger than 1, which leads to the absence of formation of air cavity and a flow with much lower inertial effects. Similarly, Goda et al 6 considered a downward injection but in Newtonian fluids with much lower injection flow rates (Q max ≈ 0.18 m 3 /h) and a different reactor geometry with a cylindrical shape and a much larger height clearance. They as well did not observe the formation of the air cavity and focused their work on studying the effects of rotating the reactor on bubble frequencies.…”
Section: Literature Surveymentioning
confidence: 99%